Administrative Support, Teacher Professional Development, and Performance Feedback: A Literature Review on Christian Religious Education Teaching Quality: Dukungan Administratif, Pengembangan Profesional Guru, dan Umpan Balik Kinerja: Sebuah Tinjauan Pustaka tentang Kualitas Pengajaran Pendidikan Agama Kristen - Susanti Embong Bulan; Metalia Margaret (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2026)
The quality of teaching in Christian Religious Education (CRE) at the higher education level is fundamentally shaped by the interplay of administrative support, professional development opportunities, and performance feedback mechanisms. This literature review synthesizes findings from twenty-four scholarly sources published between 2014 and 2026 to examine how these three administrative pillars influence lecturer teaching quality in Indonesian Christian higher education institutions. The analysis reveals that effective educational administration functions as a driving system that creates structured learning environments, facilitates continuous professional growth, and establishes robust evaluation frameworks. Findings demonstrate that systematic academic supervision, comprehensive teaching administration completeness, and constructive performance feedback significantly enhance lecturer competence and instructional effectiveness. The study identifies that personality competence emerges as the most dominant dimension in lecturer competency implementation, while continuous academic supervision proves effective in improving teacher competence in instructional planning. The review concludes that an integrated, supportive, and flexible administrative model is essential for sustaining teaching quality improvement in CRE contexts. This research contributes a theoretical framework that connects administrative functions with pedagogical excellence, offering practical implications for institutional leaders, policymakers, and educational administrators seeking to enhance CRE teaching quality in Indonesia. Kualitas pengajaran dalam Pendidikan Agama Kristen (PAK) di tingkat perguruan tinggi secara fundamental dibentuk oleh interaksi antara dukungan administratif, peluang pengembangan profesional, dan mekanisme umpan balik kinerja. Tinjauan pustaka ini mensintesiskan temuan dari dua puluh empat sumber akademis yang diterbitkan antara tahun 2014 dan 2026 untuk mengkaji bagaimana ketiga pilar administratif tersebut memengaruhi kualitas mengajar dosen di lembaga pendidikan tinggi Kristen di Indonesia. Analisis mengungkapkan bahwa administrasi pendidikan yang efektif berfungsi sebagai sistem penggerak yang menciptakan lingkungan belajar terstruktur, memfasilitasi pertumbuhan profesional berkelanjutan, dan membangun kerangka evaluasi yang kokoh. Temuan menunjukkan bahwa supervisi akademis yang sistematis, kelengkapan administrasi pengajaran yang komprehensif, dan umpan balik kinerja yang konstruktif secara signifikan meningkatkan kompetensi dosen dan efektivitas pengajaran. Studi ini mengidentifikasi bahwa kompetensi kepribadian muncul sebagai dimensi yang paling dominan dalam implementasi kompetensi dosen, sementara supervisi akademis yang berkelanjutan terbukti efektif dalam meningkatkan kompetensi guru dalam perencanaan pembelajaran. Tinjauan ini menyimpulkan bahwa model administratif yang terintegrasi, suportif, dan fleksibel sangat penting untuk mempertahankan peningkatan kualitas pengajaran dalam konteks PAK. Penelitian ini berkontribusi pada kerangka teoretis yang menghubungkan fungsi administratif dengan keunggulan pedagogis, menawarkan implikasi praktis bagi para pemimpin lembaga, pembuat kebijakan, dan administrator pendidikan yang berupaya meningkatkan kualitas pengajaran PAK di Indonesia.